KEBIJAKAN PENGELOLAAN LINGKUNGAN KAWASAN INDUSTRI SESUAI PROPER KLHK PERINGKAT HIJAU (STUDI KASUS DI KAWASAN INDUSTRI JABABEKA BEKASI) - Temmy Wikaningrum; Bambang Pramudya Noorachmat; Erliza Noor (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2015)
Environmental management in industrial estate is the strategic policy model which is needed to be developed referring to the Indonesian Government Decree number 24 year 2009, that state almost all of the new industrial developments should be located in industrial estate. The complexity in this environmental management was approached by “green rating” of PROPER’s criteria regulated by Ministry of Environment & Forestry (KLHK). PROPER is the assessment program of company performance rating in environmental management. Green rating is classified by PROPER in terms of beyond compliance performance. The result of the case study in Jababeka Industrial Estate (KIJA) Bekasi, based on its environmental situational analysis year 2014 by multidimensional scaling (MDS) method, showed that only the management dimension had a sustainability performance. The results of prospective analysis on leverage factors of MDS showed that the key factors of the environmental management model were (1) DRKPL (summary document of environmental management performance), (2) implementation of water conservation and reducing water pollution program, (3)funding for water conservation, (4) monitoring and evaluation of community development program, (5) implementation of 3R (reduce, reuse, recycle) programs of hazardous waste, (6) technology of 3R, and (7) benchmarking. Based on the key parameters and referred to the possibilities conditions, three scenarios have been developed to approach the implementative policy. The moderate scenario was recommended to be the right policy in term of consideration of technology, funding availability, time of implementation and organization skills.Keywords: environmental management, industrial estate, jababeka, proper KLHK